2004
DOI: 10.1002/tea.10131
|View full text |Cite
|
Sign up to set email alerts
|

Crossing cultural borders into science teaching: Early life experiences, racial and ethnic identities, and beliefs about diversity

Abstract: The purpose of this ethnographic study was to explore the development of belief systems as related to racial and ethnic identities of preservice teachers as they crossed cultural borders into science teaching. Data were collected throughout a yearlong teacher preparation program to learn how early life experiences and racial and ethnic identities of preservice teachers influenced both their beliefs about diversity in science classrooms and science teaching pedagogy. Case studies of three preservice teachers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 26 publications
0
27
0
3
Order By: Relevance
“…Researchers have found that early life experiences and conceptions of self can make identifying and critiquing long-held views about who students are and how they should be taught difficult (Brand & Glasson, 2004). Beginning teachers may embrace the notion of science and mathematics for all, but they still struggle to start instruction from the knowledge, interests, and experiences of their students (Bianchini & Cavazos, 2007;Simmons et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that early life experiences and conceptions of self can make identifying and critiquing long-held views about who students are and how they should be taught difficult (Brand & Glasson, 2004). Beginning teachers may embrace the notion of science and mathematics for all, but they still struggle to start instruction from the knowledge, interests, and experiences of their students (Bianchini & Cavazos, 2007;Simmons et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For most studies that address some aspect of a subject-matter identity of teachers in science education, they predominantly deal with secondary and middle school teachers (see examples, Bianchini, Cavazos, & Helms, 2000;Brand & Glasson, 2004;Eich & Reed, 2002;Enyedy, Goldbergh, & Welsh, 2005;Helms, 1998;Proweller & Mitchener, 2004); very few studies actually deal with elementary teachers in their construction of a science teacher identity (see exceptions, Lunn & Solomon, 2000;Rivera Maulucci, 2008). Unlike secondary teachers of science or majors of science, elementary teachers' identities in science are far from a strong sense of self as a science person or a tight relationship with the professional identity of science.…”
Section: Subject-matter Teacher Identitymentioning
confidence: 99%
“…The few research articles that were identified as using a cultural lens to study teacher preparation generally employed a discontinuous view of culture and made reference to cultural borders, mismatches, and conflicts. For example, Brand and Glasson (2004) used the idea of border crossing to explore the experiences of preservice science teachers when teaching students from cultural backgrounds different from theirs.…”
Section: Culture(s) As Bounded Social Worldsmentioning
confidence: 99%